Delay of the reverse pedicled venous island flap: Clinical applications. Issue 5 (October 2013) - Ueda, Koichi; Nuri, Takashi; Akamatsu, Jun; Sugita, Naoya; Otani, Kazuhiro; Yamada, Akira
Abstract In patients with hand or foot injuries, the delay procedure of the reverse pedicled venous flap was applied, including the loose areolar tissue around the pedicle vein. As preliminary clinical observations, five patients were treated with delay and the results compared with those of four patients without delay. The delay procedures were two types: type 1 was circumferential incision with ligature of the proximal vein, and type 2 was a bipedicled flap without ligature of the pedicle vein. Two weeks later, the flap was transferred to the defect. In the patients treated without delay, the maximum limit of the perfectly survived flap sizes was 4.0 × 2.0 cm. However, in the patients treated with delay, the perfectly survived sizes were 5.0 × 3.0 cm and 10 × 4.0 cm in type 1 delay and 12 × 5.0 cm in type 2 delay. The delay procedure appeared to stabilise the reverse pedicled venous flap and to expand its clinical applications.